Old Armenian Phonemic System According to Edward Aghayan - SHAHVERDYAN, TEREZA (Bulletin of Yerevan University B: Philology, 2021)
“Grabar grammar” by Edward Aghayan is considered to be a valuable study which presents the phonetic peculiarities of the 5th century classical Grabar, their phonemic values, primary and secondary characteristic features, activities’ restrictions and the like. The distinguished scholar had a lot of difficulties in his practice for he first of all dealt with non-living (so-called dead) language and therefore couldn’t give reasons for his achievements through experimental researches. Besides, the original language material was subject to perversions. However, Edward Aghayan, as a real talented scholar, was able to give an answer to intricate questions. His work is of great scientific value in accordance with various researches on General linguistics, Comparative grammar and Historical grammar, Modern grammar and Dialectology.
Keywords: Сlassical Grabar, literary language, vernacular language, laut, phonetics, phonem, phonemics, phonology, distinctive feature, diphtong, triphtong, diphtongoid